Inference Methods for Spatial Variation in Species Richness and Community Composition When Not All Species Are Detected - James D. Nichols; Thierry Boulinier; James E. Hines; Kenneth H. Pollock; John R. Sauer (Conservation Biology, 1998)
Inferences about spatial variation in species richness and community composition are important both to ecological hypotheses about the structure and function of communities and to community‐level conservation and management. Few sampling programs for animal communities provide censuses, and usually some species in surveyed areas are not detected. Thus, counts of species detected underestimate the number of species present. We present estimators useful for drawing inferences about comparative species richness and composition between different sampling locations when not all species are detected in sampling efforts. Based on capture‐recapture models using the robust design, our methods estimate relative species richness, proportion of species in one location that are also found in another, and number of species found in one location but not in another. The methods use data on the presence or absence of each species at different sampling occasions (or locations) to estimate the number of species not detected at any occasions (or locations). This approach permits estimation of the number of species in the sampled community and in subsets of the community useful for estimating the fraction of species shared by two communities. We provide an illustration of our estimation methods by comparing bird species richness and composition in two locations sampled by routes of the North American Breeding Bird Survey. In this example analysis, the two locations (and associated bird communities) represented different levels of urbanization. Estimates of relative richness, proportion of shared species, and number of species present on one route but not the other indicated that the route with the smaller fraction of urban area had greater richness and a larger number of species that were not found on the more urban route than vice versa. We developed a software package, COMDYN, for computing estimates based on these methods. Because these estimation methods explicitly deal with sampling in which not all species are detected, we recommend their use for addressing questions about species richness and community composition. Métodos de Inferencia sobre Variación Espacial en la Riqueza de Especies y la Composición de Comunidades Cuando la Totalidad de las Especies no es Detectada Las inferencias sobre variación espacial en la riqueza y composición de especies en comunidades son importantes tanto para el planteamiento de hipótesis ecológicas sobre la estructura y función de comunidades como para la conservación y manejo a nivel de comunidad. Pocos programas de muestreo de comunidades de animales proveen censos y usualmente algunas especies de las zonas muestreadas no son detectadas. Por lo tanto, los conteos de especies detectadas subestiman el número de especies presentes. Presentamos estimadores útiles para establecer inferencias sobre la riqueza comparativa de especies y la composición de especies entre diferentes localidades de muestreo cuando no todas las especies presentes son detectadas por los esfuerzos del muestreo. Nuestros métodos estiman la riqueza relativa de especies, la proporción de especies en una localidad y que son localizadas también en otra localidad y el número de especies encontradas en una localidad pero no en otra, en base a modelos de diseño robusto de captura‐recaptura. Los métodos utilizan datos de la presencia y ausencia de cada especie en diferentes ocasiones de muestreo (o diferentes localidades). Para estimar el número de especies no detectadas en ninguna ocasión (o localidad). Esta aproximación permite estimar el número de especies en la comunidad muestreada, así como en fragmentos de la comunidad, mismos que son útiles para la estimación de la fracción de especies compartidas por dos comunidades. Proveemos una ilustración de nuestros métodos de estimación al comparar la riqueza de especies de aves y su composición en dos localidades muestreadas por el Estudio de Rutas de Aves Reproductoras de Norteamérica (North American Breeding Bird Survey). En este ejemplo, las dos localidades ( y las comunidades de aves asociadas) representan diferentes niveles de urbanización. Estimaciones de la riqueza relativa, proporción de especies compartidas y el número de especies presentes en una ruta pero ausentes en otra, indicaron que la ruta con la fracción más pequeña de área urbana tuvo una riqueza mayor y un número mayor de especies no fueron encontradas en la ruta con más espacio urbano. Desarrollamos un paquete de cómputo, COMDYN, para determinar estimaciones basadas en estos métodos. Debido a que estos métodos de estimación pueden lidiar con muestreos en los cuales no todas las especies son detectadas, recomendamos su uso para abordar preguntas sobre la riqueza y composición de especies en comunidades.